First record of the genus Graptopeltus Stål (Hemiptera: Heteroptera: Rhyparochromidae) from the Korean Peninsula, with description of a new species - Kim, Junggon; Lee, Hodan; Jung, Sunghoon (Zootaxa, 2016)
The genus Graptopeltus Stål is reported from the Korean Peninsula for the first time with a new species Graptopeltus koreanus sp. nov. Morphological information such as diagnosis and description including male genitalia, and biological note are presented with illustrations and photographs. A key to Graptopeltus species is provided.